Rozpowszechnianie prasy lokalnej na przykładzie powiatu polickiego w województwie zachodniopomorskim - Urbas, Michał (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2010)
The paper presents partial results of the research into the local press the author has carried out in theWestern Pomeranian province. Adetailed analysis concerns the titles published in the territorial units at a district level. There are 18 of those, including three towns with district status, in the Western Pomeranian province. The results presented are based on extensive qualitative and quantitative surveys. The diversification of the local press, its abundance, development and end are inseparably related to local entrepreneurship and the communication process in local communities. The paper comprises three parts. The first one explains the terminology of the press and press market. The second one characterizes the local community of the Police district. The third one discusses the results of qualitative surveys and presents the quantitative analysis of local press circulation.